INTEGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN PAI SEBAGAI STRATEGI PENGUATAN MODERASI BERAGAMA di SMAN 7 JAKARTA - Afifah, Nuraqilah; Inah; Djuhaeri; Fatmah Rizkiyah; Muhammad Riyad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education (PAI) learning at the secondary school level still tends to be normative and universal, so it is not fully responsive to the social and cultural context of students. This study aims to examine the implementation of the integration of local wisdom in PAI learning as an effort to strengthen the values ​​of religious moderation. This study departs from the gap between the ideal concept of religious moderation and its learning practices in schools, and positions local wisdom as a medium connecting religious teachings and social harmony in a pluralistic society. The study uses a qualitative approach with a case study design conducted at SMAN 7 Jakarta. Data collection was conducted through learning observations, semi-structured interviews with PAI teachers and 12th-grade students, and analysis of supporting documents. Data analysis refers to the interactive model of Miles and Huberman with triangulation techniques to ensure data validity. The results show that the integration of local wisdom is carried out contextually through case study methods and discussions, by linking the values ​​in the Mangkeng and Munggahan Ceremonial traditions such as mutual cooperation and togetherness with the principles of religious moderation. This approach encourages students to assess cultural practices proportionally and develop dialogical and respectful attitudes. The research results show that the integration of local wisdom is carried out contextually through case study and discussion methods, by linking values ​​in the Mangkeng and Munggahan Ceremonial traditions, such as mutual cooperation and togetherness, with the principles of religious moderation. This approach encourages students to assess cultural practices proportionally and develop a dialogical and respectful attitude. The research findings indicate an increase in students' appreciation of cultural diversity and a decrease in rigid assessment attitudes. The successful implementation is supported by a conducive school program and teachers' dialogical competence in managing learning.